Pengaruh Kecerdasan Emosi Terhadap Produktifitas Kerja Karyawan Pada Fungsi Operasi dan Penunjang PT. Pertamina (Persero) Unit Pengolahan Balongan Indramayu - Zainal Mustafa Eq; Agus R (Sinergi: Kajian Bisnis dan Manajemen, 2007)
This research was intended to investigate about the Working Productivities, especially of employees at the operational and supporting functions. The low working productivites at PT. Pertamina is caused by the low EQ of the Employees. Based on the research hypothesis, using descriptive analysis and inferential analysis, F test dan t test from the multiple linear regression and correlation, it was concluded that: a) The EQ of the employees was relatively low. b) The working productivity was also low. c) the effect of EQ on the working productivity was indicated by R2 = 0.962 with F = 535.204 and significance level of 0.000. d) Based on the partial regression coefficient of the EQ dimension, the significance influence was found. Meanwhile social skill was the most (dominant) influential variable on the working productivity.Keywords: Emotional Quotient and Working Productiviies.